Exploring the Portrayal of Social Taboos in Bangladeshi TV Advertisements - Mondal, Uzzwal Kumar; Khatun, Most. Makdura (The Jahangirnagar Review Part-C, 2025)
This research examines how social taboos are represented in Bangladeshi TV advertisements. Four advertisements, each addressing a different type of social taboo, were selected as samples to reflect societal issues. The study mainly employs critical discourse analysis theory combined with quantitative content analysis methods. The findings show that all the advertisements effectively highlight and introduce the social taboos that exist in our society using different colors, symbols and background music based on taboos. But some of them fail to convey proper message to challenge the taboos and root them out of society. The study also notes a lack of representation of rural areas of the country, while most scenes portray urban settings. Finally, the study suggests a greater focus on solution-oriented advertisements that raise awareness and encourage societal change.